ALTERNATIVE WAYS OF RESOLVING CRIMINAL LAW CONFLICTS REGARDING CORRUPTION CRIMINAL OFFENSES - Sysak, Vladyslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to comprehensively study and analyze alternative methods for resolving criminal-legal conflicts with the aim of improving the legal framework regulating plea agreements in criminal proceedings related to corruption offenses and offenses linked to corruption. Special attention is given to exploring the potential for effective application of plea agreements as a means to optimize criminal procedures, reduce the burden on the judicial system, and ensure fair and timely justice. Research methods: the research employs logical-legal, formal-legal, cognitive-analytical, comparative-legal analysis, deduction, and other methods. Results: the effective application of plea agreements can have a preventive impact, as the simplified procedure for holding individuals accountable and mitigating punishment due to cooperation with law enforcement encourages prompt and fair resolution of criminal-legal conflicts. The essence of criminal-legal conflict and the application of current legislation in this context were analyzed. It was found that plea agreements promote judicial efficiency, reduce the burden on courts, and incentivize collaboration between defendants and law enforcement. Discussion: alternative methods for resolving criminal-legal conflicts are gaining increasing significance in the modern legal system of Ukraine, particularly in cases related to corruption offenses. Plea agreements have proven their efficiency in various jurisdictions as a tool to expedite criminal processes and foster cooperation. However, in Ukraine, the use of plea agreements in corruption cases remains limited due to legislative constraints. Recent reforms aim to address these limitations by introducing more flexible legal mechanisms to enhance the effectiveness of plea agreements in combating corruption.